(untitled) (Research, Society and Development, 2025)
Objective: To investigate the profile of PEP/HIV users at the UPA in Icoaraci, Belém, Pará. Methodology: Cross-sectional, retrospective, exploratory research, with a time frame between 2022 and 2024, using medical records for sociodemographic characterization, among others. Data were analyzed using descriptive and inferential statistics, including measures of central tendency and variability, adopting a p-value <0.05 as the criterion for significance analysis in the Chi-square (X²) and Williams’ G tests. Results: 414 PEP requests were registered, the majority of which were male (60.0%), heterosexual (60.0%), and cisgender (85.5%). They are individuals aged 20 to 29 years (50.0%) and 30 to 39 years (33.4%). The most common circumstance of exposure was consensual sexual intercourse (53.0%). Conclusion: Higher exposure was observed in the months of March, April, May, July, and December, a fact that may be related to seasonal events or increased sexual activity. The results point to the need for more targeted sexual health education campaigns, adapted to prevalent risk factors. Furthermore, knowledge of the periods of highest demand for prophylaxis can help optimize the service and access to PEP.